The use of a New Bone Graft Stabilizing Material for Ridge Augmentation - Salah, Khaled Ben; Radhakrishnan, Rohit (Journal of Orofacial Research, 2013)
Patients often present for treatment with complete dentures or implants after alveolar ridge resorption has taken place. In such cases, clinicians are obligated to perform advancedaugmentation procedures to reconstruct lost bone to aid in denture retention or to place implants in a prosthetically driven position. Procedures used to augment horizontal as well asvertical bone deficiencies include different types of bone grafts, usually in conjunction with a barrier membrane. The function of the barrier membrane is to stabilize the bone graft and to exclude epithelial and connective tissue cells from the healing area. In this report, we present the case of a male patient with an irregular alveolar ridge and a Seibert’s class I ridge defect, who was treated successfully by alveoloplasty and localized ridge augmentation using a bovine bone graft mixed with a new stabilizing material, which did away with the stability problems of using bone grafts alone.